2017
DOI: 10.1111/cas.13231
|View full text |Cite
|
Sign up to set email alerts
|

Integrated functions of membrane‐type 1 matrix metalloproteinase in regulating cancer malignancy: Beyond a proteinase

Abstract: Membrane‐type 1 matrix metalloproteinase (MT1‐MMP) is expressed in different types of invasive and proliferative cells, including cancer cells and stromal cells. MT1‐MMP cleaves extracellular matrix proteins, membrane proteins and other pericellular proteins, thereby changing the cellular microenvironment and regulating signal activation. Critical roles of protease activity in cancer cell proliferation, invasion and metastasis have been demonstrated by many groups. MT1‐MMP also has a non‐protease activity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 67 publications
1
46
1
Order By: Relevance
“…HIF promotes the expression of many genes, including MT1-MMP and MT1-MMP expression, and HIF activation might form a positive feedback loop in both mesenchymal and cancer cells. 16 These results support our data that levels of HIF-1a and MT1-MMP mRNAs significantly decrease in Anxa1-knocked down versus control Caki-1 cells (Fig. 5).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…HIF promotes the expression of many genes, including MT1-MMP and MT1-MMP expression, and HIF activation might form a positive feedback loop in both mesenchymal and cancer cells. 16 These results support our data that levels of HIF-1a and MT1-MMP mRNAs significantly decrease in Anxa1-knocked down versus control Caki-1 cells (Fig. 5).…”
Section: Discussionsupporting
confidence: 90%
“…Others have shown that MT1-MMP is a key regulator of mesenchymal cell activity. 16 The same study also showed that the cytoplasmic tail of MT1-MMP binds FIH-1 and promotes a stable FIH-1-Mint3 interaction. Mint3-bound FIH cannot hydroxylate HIFa.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Specifically, protease-induced breakdown of the ECM components is essential for tumor cells to across tissue barriers [4,5]. ADAMTS (a disintegrin-like and metalloproteinase with thrombospondin motifs) is a family of extracellular metalloproteinases which was first identified in 1997.…”
Section: Introductionmentioning
confidence: 99%